The Effect of Race and Chronic Obstructive Pulmonary Disease on Long-Term Survival after Coronary Artery Bypass Grafting - Efird, Jimmy T.; O'Neal, Wesley T.; Anderson, Curtis A.; O'Neal, Jason B.; Kindell, Linda C.; Ferguson, T. B.; Chitwood, W. R.; Kypson, Alan P. (Frontiers in Public Health, 2013)
Background: Chronic obstructive pulmonary disease (COPD) is a known predictor of decreased long-term survival after coronary artery bypass grafting (CABG). Differences in survival by race have not been examined. Methods: A retrospective cohort study was conducted of CABG patients between 2002 and 2011. Long-term survival was compared in patients with and without COPD and stratified by race. Hazard ratios (HR) and 95% confidence intervals (95%CI) were computed using a Cox regression model. Results: A total of 984 (20%) patients had COPD (black n=182; white n=802) at the time of CABG (N=4,801). The median follow-up for study participants was 4.4 years. White but not black race was observed to be a statistically significant predictor of decreased survival among COPD patients (no COPD: HR=1.0; white COPD: adjusted HR=1.5, 95%CI=1.3-1.7; black COPD: adjusted HR=1.2, 0.90-1.7). Conclusion: Contrary to the expected increased risk of mortality among black COPD patients in the general population, a similar survival disadvantage was not observed in our CABG population.